PENINGKATAN PERAN TUTOR DENGAN AKTUALISASI DIRI MAHASISWA KEPERAWATAN DALAM PROSES TUTORIAL (SEVEN JUMPS) PADA PRODI ILMU KEPERAWATAN DI FAKULTAS KESEHATAN DAN MIPA UNIVERSITAS MUHAMMADIYAH SUMATERA - Irma Fidora, Ropika Ningsih, (Menara Ilmu, 2018)
The role of the tutor is very important, because the tutor is one of the most dominant group in learning process to achieve a purpose, while self actualization is a human instinctive need to do best their. This study is focused to determine students' perceptions of the tutor's role in the process of self-actualization student tutorial in PSIK. Based on observation is sometimes student with a learning pattern of the discussion, the students more silent than speak up an opinion in their discussion and self-actualization is less good student, because the student is shy and also less an understanding of the tutorial scenario. Results of univariate study showed that students' perceptions of the role of the tutor is PSIK more than most (85.9%) the good tutor role, while the perception of students toward self-actualization PSIK students showed that the majority (93.8%) self-actualization good student. Based on chi-squere results indicate that there is a relationship between the role of the tutor with self-actualization PSIK student in 2014 with p = 0.007. This research is a descriptive correlative with a cross-sectional approach. The study was conducted from March to August 2018 through the distribution of questionnaires to independent and dependent variables. The samples is 77 respondent. Engineering samples are used is total sampling and tested using chi squere. The instrument used was a questionnaire that is based on theory Harsono. Analysis of the data in this study using a frequency distribution. The conclusion of this study indicate that the role of the tutor has a significant relationship to student self-actualization. It is expected that the role of the tutor can perform its role well and good self-actualization of students in order to reach the desired goal. Keywords: Perception, The role of the tutor, the Student Self Actualization.